Preparation method and application of solid waste-based 3D printing concrete

CN118515456BActive Publication Date: 2026-10-09QINGDAO AGRI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410769492.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2024-05-07
Filing Date
2024-06-14
Publication Date
2026-10-09
Estimated Expiration
2044-06-14

AI Technical Summary

Technical Problem

本发明有效克服了钢渣的体积安定性不良的问题,使其能够适于制备3D打印混凝土

Benefits of technology

本发明采用聚羧酸减水剂对钢渣细骨料进行处理,使钢渣中的游离氧化钙、氧化镁与聚羧酸减水剂上的羧基发生酸碱反应,一方面消除了具有体积膨胀特性的游离氧化钙、氧化镁,从而消除所造成的钢渣体积安定性不良的问题。另一方面,所述聚羧酸减水剂是通过其主链吸附在钢渣上,与所述氧化钙、氧化镁发生反应的羧基位于聚羧酸减水剂的支链上,反应后所述羧基转换为羧基根,因此,反应后不影响所述聚羧酸减水剂在钢渣上的吸附,并仍然可以利用支链的空间位阻效应减小钢渣颗粒间的接触,提高颗粒分散性,从而增加钢渣的流动性,防止钢渣吸水造成混凝土浆料流动性降低,一方面不利于浆料的输送,另一方面会影响打印后混凝土结构的强度。同时,钢渣中含有一定量的C3S等具有胶凝特性的物质,所述支链上的极性基团还会形成溶剂化水膜,有助于增加钢渣颗粒与所述拌和水之间的接触,从而促进所述C3S进行水化反应,在混凝土中形成更多的胶凝物质,提高3D打印混凝土结构的强度。进一步地,所述游离氧化钙、氧化镁与聚羧酸减水剂反应后形成的钙镁离子被硬脂酸钠转换为硬脂酸钙、硬脂酸镁固体粒子,其进入所述3D打印混凝土中后可以起到良好的润滑作用,从而增加钢渣和混凝土浆料的流动性。另外,所述硬脂酸钙、硬脂酸镁固体粒子还能够起到填充作用,有助于提高混凝土结构密实性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118515456B_ABST
    Figure CN118515456B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of solid waste-based 3D printing concrete and application thereof, and the method comprises the following steps: (1) wet materials formed by uniformly mixing steel slag fine aggregates and a water solution of polycarboxylate superplasticizer are subjected to heating and steam curing treatment, then the wet materials are uniformly mixed with a sodium stearate solution and subjected to heating and steam curing treatment, and after the treatment, the wet materials are dried to obtain pretreated steel slag fine aggregates; (2) calcium salt is added into red mud slurry and stirred until the calcium salt is completely dissolved, then sodium silicate is added and the mixture is subjected to heat and ultrasonic treatment and kept warm, after the treatment, the obtained solid is dried and ground into powder, and then the powder is subjected to calcination treatment to obtain active red mud powder; and (3) silicate cement, the pretreated steel slag fine aggregates, the active red mud powder, reinforcing fibers and cellulose ether are used as raw materials, the raw materials are uniformly mixed, and then water is added and uniformly mixed to obtain 3D printing concrete. The application effectively overcomes the problem of poor volume stability of steel slag, and makes the steel slag suitable for preparing 3D printing concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D printed concrete technology, specifically to a method for preparing solid waste-based 3D printed concrete and its application. Background Technology

[0002] Concrete is an extremely important civil engineering material in modern society, serving as the primary supporting material for human societal development and construction. 3D printed concrete is a new type of concrete construction technology developed based on 3D printing technology. Its main working principle involves passing mixed concrete slurry through a 3D printing device and, under software control, extruding it according to a pre-set printing program to ultimately obtain the designed concrete component. Because this method of constructing concrete structures is not limited by the formwork, molds, and construction techniques required for traditional concrete structures, it allows for the design and construction of more complex concrete structures. Furthermore, compared to traditional construction methods, 3D printed concrete structures can significantly shorten construction time, save materials, and offer more precise dimensional control.

[0003] Fine aggregate is a major component of 3D printed concrete materials. Traditionally, fine aggregate mainly uses non-renewable natural materials such as river sand. However, the large-scale and excessive mining of river sand not only causes environmental damage but also leads to the depletion of river sand resources. Reducing dependence on river sand and finding alternatives is one of the effective measures to alleviate the above problems. Steel slag is a solid waste produced by iron and steel smelting and has advantages such as high hardness and strong compressive strength. However, steel slag contains free calcium oxide and magnesium oxide, which leads to poor volume stability. When steel slag is used as fine aggregate in concrete materials, especially in large quantities, it can easily cause cracks in the concrete structure, and in severe cases, it can cause delamination, affecting the service life and safety of the concrete structure. Therefore, steel slag is not suitable for direct use as concrete aggregate. Summary of the Invention

[0004] To address the aforementioned problems, this invention provides a method for preparing solid waste-based 3D printed concrete and its application. This invention effectively overcomes the problem of poor volume stability of steel slag, making it suitable for preparing 3D printed concrete. Specifically, the technical solution of this invention is as follows.

[0005] First, this invention discloses a method for preparing solid waste-based 3D printed concrete, comprising the following steps: (1) The wet material formed by mixing steel slag fine aggregate with an aqueous solution of polycarboxylate superplasticizer is subjected to steam curing treatment. Then the resulting mixture is mixed with sodium stearate solution and subjected to steam curing treatment again. After completion, it is dried to obtain pretreated steel slag fine aggregate.

[0006] (2) Water-soluble calcium salts were added to the red mud slurry obtained after water washing and stirred until completely dissolved. Then sodium silicate was added and the mixture was subjected to a heat treatment and ultrasonic treatment. After completion, the resulting solid was dried, ground into powder, and then the powder was calcined to obtain active red mud powder.

[0007] (3) Take the following raw materials: 70-90 parts by weight of silicate cement, 150-210 parts by weight of the pretreated steel slag fine aggregate, 20-30 parts by weight of the activated red mud powder, 2-4 parts by weight of reinforcing fiber, and 0.18-0.32 parts by weight of cellulose ether. Mix the above raw materials evenly and add mixing water at a water-cement ratio of 0.38-0.45 and stir evenly to obtain 3D printing concrete slurry.

[0008] Further, in step (1), the material-to-liquid ratio of the steel slag fine aggregate to the aqueous solution of polycarboxylate superplasticizer is 1g:3~5ml. The mass fraction of the aqueous solution of polycarboxylate superplasticizer is 7~15%.

[0009] Furthermore, in step (1), the heating temperature is 65~80℃ and the steam curing time is 4~6 hours.

[0010] Further, in step (1), the ratio of the mixture to the sodium stearate solution is 1g:1~2ml. Optionally, the mass fraction of the sodium stearate solution is 2~3%. To accelerate the dissolution of sodium stearate, hot water can be used to prepare the sodium stearate solution.

[0011] Furthermore, in step (1), the heating temperature in the process of reheating and steam curing is 65~80℃ and the steam curing time is 1~1.5 hours.

[0012] Furthermore, in step (1), the drying temperature is 80~100℃, and the product is dried to a constant weight.

[0013] Furthermore, in step (1), the particle size distribution of the pretreated steel slag fine aggregate is between 0.3 and 1 mm.

[0014] Further, in step (2), the water content of the red mud slurry is 20-30%, and the mass fraction of the calcium salt is 15-25%. Optionally, the calcium salt includes at least one of calcium nitrate, calcium acetate, etc.

[0015] Further, in step (2), the sodium silicate is added according to a Ca:Si molar ratio of 2~3:1.

[0016] Further, in step (2), the heating temperature is 40~50℃, and the heat preservation reaction time is 6~10 hours. Optionally, the ultrasonic power is 300~400W.

[0017] Furthermore, in step (2), the calcination treatment is carried out at a temperature of 550~680℃ for 1~2 hours.

[0018] Furthermore, in step (2), the fineness of the activated red mud powder is 100~200 mesh.

[0019] Further, in step (3), the reinforcing fiber includes at least one of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber, glass fiber, carbon fiber, basalt fiber, etc. Optionally, the length of the fiber is 5~12mm.

[0020] Further, in step (3), the cellulose ether includes at least one of hydroxymethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, etc.

[0021] Secondly, this invention discloses the application of solid waste-based 3D printed concrete obtained by the above preparation method in fields such as building engineering, water conservancy engineering, marine engineering, and road engineering.

[0022] Compared with the prior art, the present invention has at least the following beneficial technical effects: This invention uses a polycarboxylate superplasticizer to treat fine aggregates in steel slag. This causes an acid-base reaction between the free calcium oxide and magnesium oxide in the steel slag and the carboxyl groups on the polycarboxylate superplasticizer. On one hand, this eliminates the volume expansion characteristics of the free calcium oxide and magnesium oxide, thus addressing the problem of poor volume stability in the steel slag. On the other hand, the polycarboxylate superplasticizer is adsorbed onto the steel slag via its main chain. The carboxyl groups that react with the calcium oxide and magnesium oxide are located on the branches of the polycarboxylate superplasticizer. After the reaction, these carboxyl groups are converted into carboxyl groups. Therefore, the reaction does not affect the adsorption of the polycarboxylate superplasticizer on the steel slag, and the steric hindrance effect of the branches can still be used to reduce the contact between steel slag particles, improving particle dispersibility and thus increasing the fluidity of the steel slag. This prevents the steel slag from absorbing water, which would reduce the fluidity of the concrete slurry, hindering slurry transport and affecting the strength of the printed concrete structure. Meanwhile, the steel slag contains a certain amount of C3S and other substances with cementing properties. The polar groups on the branched chains also form a solubilized water film, which helps increase the contact between the steel slag particles and the mixing water, thereby promoting the hydration reaction of the C3S and forming more cementing substances in the concrete, thus improving the strength of the 3D printed concrete structure. Furthermore, the calcium and magnesium ions formed after the reaction of the free calcium oxide and magnesium oxide with the polycarboxylate superplasticizer are converted into calcium stearate and magnesium stearate solid particles by sodium stearate. These particles, after entering the 3D printed concrete, can play a good lubricating role, thereby increasing the fluidity of the steel slag and concrete slurry. In addition, the calcium stearate and magnesium stearate solid particles can also act as fillers, helping to improve the compactness of the concrete structure.

[0023] Furthermore, the 3D-printed concrete of this invention incorporates activated red mud powder. This invention adds water-soluble calcium salts and sodium silicate to the washed red mud slurry, which react to form hydrated calcium silicate (CSH). Due to the excellent cementitious properties of CSH, it firmly supports the red mud. Further calcination of the red mud results in the dehydration of the CSH, forming calcium silicate and activated red mud powder. During the hydration reaction stage of the 3D-printed concrete structure, the calcium silicate undergoes a further hydration reaction to reform hydrated calcium silicate with cementitious properties, thus giving the traditional red mud cementitious characteristics, better bonding with the concrete matrix, and improving strength. Additionally, the calcium silicate loaded on the red mud particles can induce the hydration of the silicate cement, increasing the hydration reaction rate, thereby improving the early strength of the printed concrete structure, helping to prevent deformation, and improving dimensional accuracy. Attached Figure Description

[0024] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Hereinafter, embodiments of the invention will be described in detail with reference to the accompanying drawings, wherein: Figure 1 The image shows the compressive strength test results of the 3D-printed concrete specimen prepared in Example 1 below. Detailed Implementation

[0025] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. The technical solution of the present invention will now be further described with reference to specific embodiments.

[0026] Example 1 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) Steel slag fine aggregate with a continuous particle size between 0.3 and 1.0 mm was mixed with a 10% (w / w) aqueous solution of polycarboxylate superplasticizer at a material-to-liquid ratio of 1 g:4 ml to form a wet material. The wet material was then placed in a sealed container and heated to 70°C in a water bath for 5 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting mixture was mixed with a 3% (w / w) sodium stearate solution at a ratio of 1 g:1.5 ml and stirred evenly. The mixture was then heated again in a sealed container at 70°C for 1 hour, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting solid was dried at 80°C to constant weight to obtain pretreated steel slag fine aggregate for later use.

[0027] (2) After washing the sintered red mud with water to form a red mud slurry with a water content of 30%, place it in a reaction vessel, then add calcium salt (calcium nitrate) and stir until it is completely dissolved, and the mass fraction of calcium salt in the red mud slurry is 20%. Then, add sodium silicate solution with a mass fraction of 10% according to the Ca:Si molar ratio of 3:1. After completion, seal the reaction vessel and heat it in a water bath to 50°C and keep it at that temperature for 6 hours, and perform ultrasonic treatment during the reaction (ultrasonic power of 300W). After completion, heat and dry the obtained solid, then mechanically grind it and pass it through a 200-mesh sieve. Heat the obtained powder to 650°C and calcine it for 1.5 hours to obtain active red mud powder for later use.

[0028] (3) Weigh the following raw materials: 85 parts by weight of 42.5 ordinary silicate cement, 200 parts by weight of the pretreated steel slag fine aggregate described in this embodiment, 25 parts by weight of the active red mud powder described in this embodiment, 3 parts by weight of polypropylene fiber with a length of 5 mm, and 0.3 parts by weight of hydroxypropyl methylcellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.42 and stir for 3 minutes until uniform to obtain 3D printing concrete slurry.

[0029] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 197 mm.

[0030] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). Figure 1 The results were: 1-day compressive strength = 14.53 MPa, 28-day compressive strength = 44.08 MPa.

[0031] Example 2 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) Steel slag fine aggregate with a continuous particle size between 0.3 and 1.0 mm was mixed with an aqueous solution of 7% polycarboxylate superplasticizer at a material-to-liquid ratio of 1 g: 5 ml to form a wet material. The wet material was then placed in a sealed container and heated to 80°C in a water bath for 4 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting mixture was mixed with a 2% sodium stearate solution at a ratio of 1 g: 2 ml and stirred evenly. The mixture was then heated again in a sealed container at 80°C for 1 hour, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting solid was dried at 90°C to constant weight to obtain pretreated steel slag fine aggregate for later use.

[0032] (2) After washing the sintered red mud with water to form a red mud slurry with a water content of 35%, place it in a reaction vessel, then add calcium salt (calcium nitrate) and stir until it is completely dissolved, and the mass fraction of calcium salt in the red mud slurry is 15%. Then, add sodium silicate solution with a mass fraction of 10% according to the Ca:Si molar ratio of 3:1. After completion, seal the reaction vessel and heat it in a water bath to 40°C and keep it at that temperature for 10 hours, and perform ultrasonic treatment during the reaction (ultrasonic power of 300W). After completion, heat and dry the obtained solid, then mechanically grind it and pass it through a 150-mesh sieve. Heat the obtained powder to 680°C and calcine it for 1 hour to obtain active red mud powder for later use.

[0033] (3) Weigh the following raw materials: 70 parts by weight of 42.5 ordinary silicate cement, 150 parts by weight of the pretreated steel slag fine aggregate described in this embodiment, 20 parts by weight of the active red mud powder described in this embodiment, 2 parts by weight of polyethylene fiber with a length of 10 mm, and 0.18 parts by weight of hydroxymethyl cellulose. Mix the above raw materials and stir for 3 minutes. Then add mixing water at a water-cement ratio of 0.38 and stir for 3 minutes until uniform to obtain 3D printing concrete slurry.

[0034] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 192 mm.

[0035] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 16.61 MPa, 28-day compressive strength = 45.79 MPa.

[0036] Example 3 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) Steel slag fine aggregate with a continuous particle size between 0.3 and 1.0 mm was mixed with an aqueous solution of 15% polycarboxylate superplasticizer at a material-to-liquid ratio of 1 g: 5 ml to form a wet material. The wet material was then placed in a sealed container and heated to 65°C in a water bath for 6 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting mixture was mixed with a 3% sodium stearate solution at a ratio of 1 g: 1 ml and stirred evenly. The mixture was then heated again in a sealed container at 65°C for 1.5 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting solid was dried at 100°C to constant weight to obtain pretreated steel slag fine aggregate for later use.

[0037] (2) After washing the sintered red mud with water to form a red mud slurry with a water content of 25%, place it in a reaction vessel, then add calcium salt (calcium acetate) and stir until it is completely dissolved, and the mass fraction of calcium salt in the red mud slurry is 25%. Then, add sodium silicate solution with a mass fraction of 15% according to the Ca:Si molar ratio of 2:1. After completion, seal the reaction vessel and heat it in a water bath to 45°C and keep it at that temperature for 8 hours, and perform ultrasonic treatment during the reaction (ultrasonic power of 400W). After completion, heat and dry the obtained solid, then mechanically grind it and pass it through a 100-mesh sieve. Heat the obtained powder to 550°C and calcine it for 2 hours to obtain active red mud powder for later use.

[0038] (3) Weigh the following raw materials: 90 parts by weight of 42.5 ordinary silicate cement, 210 parts by weight of the pretreated steel slag fine aggregate described in this embodiment, 30 parts by weight of the active red mud powder described in this embodiment, 4 parts by weight of basalt fiber with a length of 12 mm, and 0.32 parts by weight of hydroxypropyl cellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.45 and stir for 3 minutes until uniform to obtain 3D printing concrete slurry.

[0039] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 194 mm.

[0040] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 14.32 MPa, 28-day compressive strength = 43.52 MPa.

[0041] Example 4 A method for preparing solid waste-based 3D printed concrete includes the following steps: Weigh the following raw materials: 85 parts by weight of 42.5 ordinary Portland cement, 200 parts by weight of steel slag fine aggregate with a continuous particle size between 0.3 and 1.0 mm, 25 parts by weight of active red mud powder prepared according to Example 1 above, 3 parts by weight of polypropylene fiber with a length of 5 mm, and 0.3 parts by weight of hydroxypropyl methylcellulose. Mix the above raw materials and stir for 5 minutes. Then, add mixing water at a water-cement ratio of 0.42 and stir for 3 minutes until homogeneous to obtain the 3D printing concrete slurry.

[0042] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 181 mm.

[0043] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 10.24 MPa, 28-day compressive strength = 30.15 MPa.

[0044] Example 5 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) Steel slag fine aggregate with a continuous particle size between 0.3 and 1.0 mm is mixed with an aqueous solution of polycarboxylate superplasticizer with a mass fraction of 10% at a material-to-liquid ratio of 1 g: 4 ml to form a wet material. The wet material is then placed in a sealed container and heated to 70°C in a water bath for 5 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting solid is dried at 80°C to constant weight to obtain pretreated steel slag fine aggregate for later use.

[0045] (2) Weigh the following raw materials: 85 parts by weight of 42.5 ordinary silicate cement, 200 parts by weight of the pretreated steel slag fine aggregate described in this embodiment, 25 parts by weight of the active red mud powder prepared according to Example 1 above, 3 parts by weight of polypropylene fiber with a length of 5 mm, and 0.3 parts by weight of hydroxypropyl methylcellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.42 and stir for 3 minutes until uniform to obtain 3D printing concrete slurry.

[0046] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 183 mm.

[0047] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 12.18 MPa, 28-day compressive strength = 42.26 MPa.

[0048] Example 6 A method for preparing solid waste-based 3D printed concrete includes the following steps: Weigh the following raw materials: 70 parts by weight of 42.5 ordinary Portland cement, 150 parts by weight of river sand fine aggregate with a particle size continuously distributed between 0.3 and 1.0 mm, 20 parts by weight of the active red mud powder prepared according to Example 2 above, 2 parts by weight of polyethylene fiber with a length of 10 mm, and 0.18 parts by weight of hydroxymethyl cellulose. Mix the above raw materials and stir for 3 minutes. Then, add mixing water at a water-cement ratio of 0.38 and stir for 3 minutes until uniform to obtain the 3D printing concrete slurry.

[0049] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 195 mm.

[0050] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 14.06 MPa, 28-day compressive strength = 44.57 MPa.

[0051] Example 7 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) After washing the sintered red mud with water and heating and drying it, it is then mechanically ground and passed through a 100-mesh sieve. The resulting powder is heated to 550℃ and calcined for 2 hours to obtain active red mud powder for later use.

[0052] (2) Weigh the following raw materials: 90 parts by weight of 42.5 ordinary silicate cement, 210 parts by weight of pretreated steel slag fine aggregate prepared according to Example 3 above, 30 parts by weight of the active red mud powder of this example, 4 parts by weight of basalt fiber with a length of 12 mm, and 0.32 parts by weight of hydroxypropyl cellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.45 and stir for 3 minutes to obtain uniform 3D printing concrete slurry.

[0053] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 191 mm.

[0054] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 10.83 MPa, 28-day compressive strength = 37.29 MPa.

[0055] Example 8 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) Steel slag and water are mixed at a ratio of 1g:5ml to form a wet material. The wet material is then placed in a sealed container and heated to 65°C in a water bath for 6 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting mixture is mixed with a 3% sodium stearate solution at a ratio of 1g:1ml and stirred evenly. The mixture is then heated again in a sealed container at 65°C for 1.5 hours, with the pressure in the container controlled between 0.15 and 0.2 MPa. After completion, the resulting solid is dried at 100°C to constant weight to obtain pretreated steel slag fine aggregate, which is ready for use.

[0056] (2) Weigh the following raw materials: 90 parts by weight of 42.5 ordinary silicate cement, 210 parts by weight of the pretreated steel slag fine aggregate described in this embodiment, 30 parts by weight of the active red mud powder prepared according to Example 3 above, 4 parts by weight of basalt fiber with a length of 12 mm, and 0.32 parts by weight of hydroxypropyl cellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.45 and stir for 3 minutes to obtain uniform 3D printing concrete slurry.

[0057] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 186 mm.

[0058] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 11.37 MPa, 28-day compressive strength = 38.21 MPa.

[0059] Example 9 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) After washing the sintered red mud with water to form a red mud slurry with a water content of 30%, place it in a reaction vessel, then add calcium salt (calcium nitrate) and stir until it is completely dissolved, and the mass fraction of calcium salt in the red mud slurry is 20%. Then, add sodium silicate solution with a mass fraction of 10% according to the Ca:Si molar ratio of 3:1. After completion, seal the reaction vessel and heat it in a water bath to 50°C and keep it at that temperature for 6 hours, and perform ultrasonic treatment during the reaction (ultrasonic power of 300W). After completion, heat and dry the obtained solid, then mechanically grind it and pass it through a 200-mesh sieve to obtain activated red mud powder for later use.

[0060] (2) Weigh the following raw materials: 85 parts by weight of 42.5 ordinary silicate cement, 200 parts by weight of pretreated steel slag fine aggregate prepared according to Example 1 above, 25 parts by weight of the active red mud powder of this example, 3 parts by weight of polypropylene fiber with a length of 5 mm, and 0.3 parts by weight of hydroxypropyl methylcellulose. Mix the above raw materials and stir for 5 minutes. Then add mixing water at a water-cement ratio of 0.42 and stir for 3 minutes to obtain uniform 3D printing concrete slurry.

[0061] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 198 mm.

[0062] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 13.94 MPa, 28-day compressive strength = 43.77 MPa.

[0063] Example 10 A method for preparing solid waste-based 3D printed concrete includes the following steps: (1) After washing the sintered red mud with water to form a red mud slurry with a water content of 35%, place it in a reaction vessel, add calcium salt (calcium nitrate) and stir until it is completely dissolved, and the mass fraction of calcium salt in the red mud slurry is 15%. After completion, seal the reaction vessel and heat it in a water bath to 40°C and keep it at that temperature for 10 hours, and perform ultrasonic treatment during the reaction (ultrasonic power of 300W). After completion, heat and dry the obtained solid, then mechanically grind it and pass it through a 150-mesh sieve. Heat the obtained powder to 680°C and calcine it for 1 hour to obtain active red mud powder for later use.

[0064] (2) Weigh the following raw materials: 70 parts by weight of 42.5 ordinary silicate cement, 150 parts by weight of pretreated steel slag fine aggregate prepared according to Example 2 above, 20 parts by weight of the active red mud powder of this example, 2 parts by weight of polyethylene fiber with a length of 10 mm, and 0.18 parts by weight of hydroxymethyl cellulose. Mix the above raw materials and stir for 3 minutes. Then add mixing water at a water-cement ratio of 0.38 and stir for 3 minutes until uniform to obtain 3D printing concrete slurry.

[0065] The fluidity of the 3D printed concrete slurry prepared in this embodiment was tested according to the "Method for Determination of Flowability of Cement Mortar" (GB / T 2419-2005), and the result was 190 mm.

[0066] The 3D-printed concrete slurry prepared in this embodiment was printed using a printing device and then cured. After solidification and hardening, specimens were cut from the slurry, and the compressive strength of the specimens was tested according to the "Test Method for Strength of Cement Mortar" (GB / T17671-2021). The results were: 1-day compressive strength = 12.33 MPa, 28-day compressive strength = 42.63 MPa.

[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing solid waste-based 3D printed concrete, characterized in that, Including the following steps: (1) The wet material formed by mixing steel slag fine aggregate with an aqueous solution of polycarboxylate superplasticizer is subjected to heating and steam curing treatment; then the resulting mixture is mixed with sodium stearate solution, and then subjected to heating and steam curing treatment again. After completion, it is dried to obtain pretreated steel slag fine aggregate; the material-liquid ratio of steel slag fine aggregate to the aqueous solution of polycarboxylate superplasticizer is 1g:3~5ml, the mass fraction of the aqueous solution of polycarboxylate superplasticizer is 7~15%, and the material-liquid ratio of the mixture to the sodium stearate solution is 1g:1~2ml; (2) Add water-soluble calcium salt to the red mud slurry obtained after water washing and stir until it is completely dissolved. Then add sodium silicate and carry out a heat preservation reaction under heating and ultrasonic treatment conditions. After completion, dry and grind the obtained solid into powder, and then calcine the powder to obtain active red mud powder. (3) Take the following raw materials: 70-90 parts by weight of silicate cement, 150-210 parts by weight of the pretreated steel slag fine aggregate, 20-30 parts by weight of the active red mud powder, 2-4 parts by weight of reinforcing fiber, and 0.18-0.32 parts by weight of cellulose ether; mix the above raw materials evenly and add mixing water at a water-cement ratio of 0.38-0.45 and stir evenly to obtain 3D printing concrete slurry.

2. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (1), the heating temperature is 65~80℃ and the steam curing time is 4~6 hours.

3. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, The sodium stearate solution has a mass fraction of 2-3%.

4. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (1), the heating temperature is 65~80℃ and the steam curing time is 1~1.5 hours.

5. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (1), the drying temperature is 80~100℃, and the product is dried to a constant weight.

6. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (1), the particle size distribution of the pretreated steel slag fine aggregate is between 0.3 and 1 mm.

7. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the water content of the red mud slurry is 20-30%, and the mass fraction of the calcium salt is 15-25%.

8. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the calcium salt includes at least one of calcium nitrate and calcium acetate.

9. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), sodium silicate is added according to a Ca:Si molar ratio of 2~3:

1.

10. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the heating temperature is 40~50℃ and the heat preservation reaction time is 6~10 hours.

11. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the ultrasonic power is 300~400W.

12. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the calcination treatment is carried out at a temperature of 550~680℃ for 1~2 hours.

13. The method for preparing solid waste-based 3D printed concrete according to claim 1, characterized in that, In step (2), the fineness of the activated red mud powder is 100~200 mesh.

14. The method for preparing solid waste-based 3D printed concrete according to any one of claims 1-13, characterized in that, In step (3), the reinforcing fiber includes at least one of polyethylene fiber, polyvinyl alcohol fiber, polypropylene fiber, glass fiber, carbon fiber, and basalt fiber.

15. The method for preparing solid waste-based 3D printed concrete according to any one of claims 1-13, characterized in that, In step (3), the length of the fiber is 5~12mm.

16. The method for preparing solid waste-based 3D printed concrete according to any one of claims 1-13, characterized in that, In step (3), the cellulose ether includes at least one of hydroxymethylcellulose, hydroxypropylcellulose, and hydroxypropylmethylcellulose.

17. The application of solid waste-based 3D printed concrete obtained by the preparation method of solid waste-based 3D printed concrete according to any one of claims 1-16 in the fields of building engineering, water conservancy engineering, marine engineering or road engineering.

Citation Information

Patent Citations

  • Method for preparing lightweight wall tile by using red mud as main raw material

    CN106977171A

  • Water-reducing steel slag modifier as well as preparation method and application thereof

    CN112358220A

  • High-temperature-resistant 3D-printing fiber concrete with steel slag waste as aggregate, and preparation method of high-temperature-resistant 3D-printing fiber concrete

    CN113173756A

  • Anti-cracking synergist suitable for solid waste-based concrete as well as preparation method and application of anti-cracking synergist

    CN116803939A